Mapping Leadership Models in Early Childhood Education Institutions and Their Influence on Organizational Commitment and Work Productivity - Abdul Kadir Jaelani; Sugito (Jurnal Pendidikan Indonesia, 2024)
The leadership model implemented by the school principal is at odds with the teacher's wishes, causing teacher performance to be unproductive, thus having an impact on the quality of educational institutions. The aim of the research is to analyze the most appropriate form of leadership and influence on organizational commitment and work productivity. This type of research is quantitative, applying survey methods using questionnaires. The research subjects were 721 kindergarten teachers. Samples were taken using the Slovin formula to obtain 236 teachers. Inferential analysis uses Structural Equation Modeling and Partial Least Squares techniques. The research results are; Participative leadership has a very good direct influence on organizational commitment. The research results prove that participative leadership, commitment has an influence on work productivity, and organizational commitment is a variable that is able to mediate participative leadership on work productivity. The participative leadership model needs to be implemented in Early Childhood Education Institutions to increase organizational commitment and its influence on work productivity. The implications of this research are can help stakeholders, such as school principals, PAUD institution managers, and policy makers, in selecting and implementing the most effective leadership model according to the institution's needs.